Mechanisms to combat administrative and financial corruption in Algeria under New fixes - Bensuilah, Amel (Journal of Human Sciences, 2021)
The phenomenon of financial and administrative corruption is one of the most prominent problems that Algeria suffers from during a certain period of time, due to many and varied reasons that have contributed to the decline of Algeria to the last ranks in all fields. This study aims to shed light on the phenomenon of corruption by defining its concept and causes, and defining the parameters of Algeria's strategy used and the extent of its success in that.